Rural economic spillovers from fish farming and agriculture in the Ayeyarwady delta - Filipski, Mateusz J.; Belton, Ben (Michigan State University, 2017)
This study reveals that aquaculture is more profitable for fish farmers than crop farming, and generates large income spillovers for the local economy, thus presenting important opportunities for rural growth. Furthermore, small-scale fish farms, while currently somewhat less productive than large farms overall, generate larger indirect spillover effects per acre of land. Viewed through an economywide lens, small-scale aquaculture has substantial potential to support smallholder livelihoods whilst creating large income spillovers that principally benefit landless households and raise rural incomes. These findings imply that any aquaculture development strategy should focus on fish farms under 10 acre in size, rather than the large-scale farm development prioritized in the past. First, small-scale farmers should be empowered to use their ponds with maximum efficiency by, for instance, facilitating access to sources of credit and information. Second, regulations should be revised to allo